A Does Media Play an Important Roles in Regional Election? A Pers Law Perspective - ZAINAL ARIFIN; Muhammad Ayman al-Akiti; Emi Puasa Handayani; Sholahuddin Al-Fatih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims to investigate the influence of press law regulations on political reporting in online media and to conduct a comparative study of press law regulations in countries that have experienced the development of online media in the political context. The research employs content analysis of political news in online media during the 2024 regional election campaign period to understand the extent of online media's influence in shaping public opinion and election outcomes. This research is expected to provide a clear vision of the role of online media in the political process and contribute new understanding to the legal regulations of the press needed to maintain the continuity of democracy.